Pengaruh Employee Engagement terhadap Workforce Agility pada Karyawan Start -Up di Indonesia - Nurhastuti, Evi Sri; Astari, Karima; Junjunan, Ilham Medal; Fazrin, Balqis Nurul (Jurnal Ilmiah Psikologi (JIPSI), 2024)
Start-up businesses are growing rapidly because Indonesia is a potential market for business people with a high productive age. Employee engagement is important to be able to adapt to various challenges. Engaged employees will respond according to the needs of the organization. The aim of this research is to determine the effect of employee engagement on workforce agility in start-up employees in Indonesia. The method used in this research is quantitative with simple regression analysis techniques. Based on the results of the analysis carried out, it shows that the p-value is smaller than 5% error (p<0.05), so H1 is accepted. The conclusion is that the employee engagement variable has a significant influence on workforce agility with a value of Fcount 118.768 > Ftable 3.398, meaning that employee engagement has a significant influence on workforce agility. The results of this research employee engagement contributes to workforce agility, can improve employee performance, improve the work environment, improve employee welfare, increase start-up competitiveness, increase employee loyalty and become the basis for developing organizational policies and programs.